2018
DOI: 10.3389/fmicb.2018.00658
|View full text |Cite|
|
Sign up to set email alerts
|

Carbapenem-Resistant E. cloacae in Southwest China: Molecular Analysis of Resistance and Risk Factors for Infections Caused by NDM-1-Producers

Abstract: Carbapenem-resistant Enterobacteriaceae (CRE) has been considered a serious global threat, but carbapenem resistance remains relatively uncommon in E. cloacae, especially in China. The aim of this study was to characterize carbapenem-resistant E. cloacae (CR-ECL) isolates from 2012 to 2016 in Southwest China. Our study revealed that 20 (15.2%) of the 132 CR-ECL isolates obtained from patients were identified as NDM-1, with most isolates carrying the IncFIIA plasmids. Notably, we initially observed that the E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Previous studies have shown the emergence of bla NDM-1 in China, with most of them being carried on the IncFIIAs-type plasmids. 17 In this study, plasmids from all the bla NDM-1carrying strains (including those in the donors and the transconjugants) also belonged to the plasmid replicon type IncFIIAs. In addition, the plasmids containing bla KPC-2 were un-typable.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have shown the emergence of bla NDM-1 in China, with most of them being carried on the IncFIIAs-type plasmids. 17 In this study, plasmids from all the bla NDM-1carrying strains (including those in the donors and the transconjugants) also belonged to the plasmid replicon type IncFIIAs. In addition, the plasmids containing bla KPC-2 were un-typable.…”
Section: Discussionmentioning
confidence: 80%
“…For conjugative assays, the rifampin-resistant E. coli EC600 strain was use as the recipient, and the transconjugants were selected on Mueller-Hinton agar plates supplemented with a combination of 32 µg/ml ampicillin and 512 µg/ml rifampin. For transformation assays, the transformants were selected on Mueller-Hinton agar plates containing 2 µg/ml MEM (Jia et al, 2018). Both the transconjugants and transformants were tested for antimicrobial susceptibilities by the VITEK2 compact system, and MICs for ETP, IPM, MEM, colistin (CS), and tigecycline (TGC) were further determined by the broth microdilution method.…”
Section: Conjugation Transformation and Plasmid Analysismentioning
confidence: 99%
“…The most alarming data was that none of these cases had a history of traveling outside Brazil, which might represent local acquisition. Our cases present common characteristics, such as low socioeconomic class, low educational background, severe clinical conditions and poor functional status, already described as risk factors for infection by co-resistant agents (6,13,14).…”
Section: Discussionmentioning
confidence: 59%